Evaluating EU Regional Policy: Many Empirical Specifications, One (Unpleasant) Result - Philipp Breidenbach; Timo Mitze; Christoph M. Schmidt (European Regional Science Association (ERSA), 2011)
Numerous studies have focused on the role of EU regional policy in fostering growth and convergence among European regions, why conducting another one? We argue that two facts are still lacking in the actual academic debate in order to get a sound empirical identification strategy and reliable results: First, one should take the theoretical underpinnings of regional growth models more serious, and second, a likewise careful account of the role of spatial dependence in the underlying data is needed. Though research has increasingly become aware of the latter point as important control factor for regional heterogeneity and omitted variables, in empirical operationalization still the ad-hoc inclusion of a hardly interpretable `catch-all' spatial lag term of the endogenous variable is the first choice. We rather follow the lines of new theoretical and empirical approaches aiming at directly quantifying interregional spillovers associated with the amount of funds granted to lagging regions and their neighborhood. The dataset includes 127 NUTS1/-2 regions within the EU15 over the decade 1997-2007. In the spotlight of the investigation are the Objective 1 payments which are provided for lagging regions with a GDP p.c. of less than 75% of the EU average. These payments shall represent the main instrument to fulfill the central aim of European regional policy, the boost of convergence and harmonic growth over the EU. They represent about two third of the whole European cohesion policy. In our estimations we run a neoclassical convergence model in mainly four different specifications. On the one hand we separate in the aspatial and spatial models. On the other hand we run additive and multiplicative applications in order to consider the right coefficient interpretations. We estimate the model in various econometric specifications to point out the effectiveness of these funding. Our results all hint to the unpleasant result that EU structural funds objective 1 funding has a remarkably little or even negative direct impact on regional growth within the EU15. The spatial funding effects turn into negative significance in the most model specifications.
Keywords: 330